Comparison of Sympathomimetics in the Correction of Arterial Hypotension during Combined Anesthesia - D. B. Borisov; O. V Krylov; A. A. Kapinos; S. V Yudin; N. A. Istomina (Общая реаниматология, 2012)
Objective: to make a comparative assessment of hemodynamic parameters when correcting combined anesthesia-induced arterial hypotension with dopamine, adrenaline, mesatone, or noradrenaline. Subjects and methods. A prospective study enrolled patients who had undergone prosthetic hip replacement under combined lumbar epidural (ropivacaine)/general (sevoflurane) anesthesia. Intravenous sympathomimetic infusion was initiated when the mean blood pressure decreased below 55 Hg mm. Cardiac index (CI) and systemic vascular resistance index (SVRI) were calculated by impedance cardiography. Fifty-six subjects (14 in each group) were selected for analysis. Results. During the study, CI remained in the normal range for all sympathomimetics. When adrenaline was administered, there was an obvious tendency to maintain blood pressure due to heart rate (HR) with preserved low SVRI. The use of mesatone caused a considerable reduction in HR. No statistically significant differences were found between the dopamine and noradrenaline groups in any of the study stages. The start of infusion of these agents was attended by SVRI normalization and HR maintenance within 60—70 beats per minute. Conclusion. The infusion of dopamine, adrenaline, mesatone, or noradrenaline to correct arterial hypotension resulting from combined epidural block/general anesthesia with sevoflurane ensures maintenance of CI within the normal range. That of noradrenaline and dopamine was ascertained to have a more balanced impact on HR and systemic vascular resistance. Key words: combined anesthesia, epidural block, hemodynamics, sympathomimetics, adrenaline, dopamine, mesatone, noradrenaline.